PEARL CULTURE—ITS POTENTIAL AND IMPLICATIONS IN INDIA - Alagarswami, K; Qasim, S Z (Indian Journal of Fisheries, 2011)
Pearl fisheries of India are of ancient origin. The pearl oyster resources are located mainlyin the Gulf of Kutch and Gulf of Mannar. They are subjected to wide fluctuations from year to year, particularly when they are exploited for natural pearls. In 1972, Vei^alodai, near Tuticorin, was selected as a site for conducting experiments on pearl oyster farming and on the development of cultured pearls. Modem method of raft culture was adopted for raising mother oysters. This method proved successful despite the trying sea conditions prevailing during the monsoon months. The survival rate of the pearl oysters in the farm was about 78 % during the first year. The oysters grew fast in the farm in certain seasons and remained healthy throughout the experiments. Fouling by different organisms was a serious problem and, if not checked properly, led to mortality of oysters. Settlement of the spats of pearl oyster occurred at the farm from May to July. At Veppalodai, the techniques of producing cultured pearls from the Indian pearl oyster, Pittctada fucata, were developed and for the first time free, spherical cultured pearls were produced. The potential and implications of pearl culture in India have bsen discussed in relation to the situations prevailing in the pearl culture industry of other parts of the world.